2012
DOI: 10.1002/qre.1465
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Coefficient of Variation Using a Variable Sampling Interval Control Chart

Abstract: The coefficient of variation (CV) is a quality characteristic that has several applications in applied statistics and is receiving increasing attention in quality control. Few papers have proposed control charts that monitor this normalized measure of dispersion. In this paper, an adaptive Shewhart control chart implementing a variable sampling interval (VSI) strategy is proposed to monitor the CV. Tables are provided for the statistical properties of the VSI CV chart, and a comparison is performed with a Fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
98
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 38 publications
1
98
1
Order By: Relevance
“…The results showed that the synthetic chart performed better than that of Kang et al (2007), but worse than Castagliola et al (2011) as long as the increasing shift in the CV is not too large. In addition, Castagliola et al (2013a) evaluated an adaptive Shewhart control chart implementing variable sampling interval strategy to monitor the process CV. Castagliola et al (2013b) proposed a Shewhart chart with supplementary run rules to monitor the CV.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the synthetic chart performed better than that of Kang et al (2007), but worse than Castagliola et al (2011) as long as the increasing shift in the CV is not too large. In addition, Castagliola et al (2013a) evaluated an adaptive Shewhart control chart implementing variable sampling interval strategy to monitor the process CV. Castagliola et al (2013b) proposed a Shewhart chart with supplementary run rules to monitor the CV.…”
Section: Introductionmentioning
confidence: 99%
“…The following example has been introduced in Castagliola et al [5] for the implementation of a VSI control chart monitoring the CV in a long production run context and will be adapted, in this paper, for a short production run context. For more information concerning this example, refer to Castagliola et al [5].…”
Section: Illustrative Examplementioning
confidence: 99%
“…For more information concerning this example, refer to Castagliola et al [5]. This example considers actual data from a die casting hot chamber process kindly provided by a Tunisian company manufacturing zinc alloy (ZAMAK) parts for the sanitary sector.…”
Section: Illustrative Examplementioning
confidence: 99%
See 1 more Smart Citation
“…In the SPC literature, Shewhart‐type control chart for monitoring the coefficient of variation (CV), which is defined as the ratio of the population standard deviation to the population mean, has already been investigated by Kang et al; subsequently, several control charts have been developed in the literature for monitoring the CV. For further details, see, for instance, Castagliola et al, Calzada and Scariano, Castagliola et al, Castagliola et al, Zhang et al, Castagliola et al, Castagliola et al, Amdouni et al, You et al, and Tran and Tran among others. For example, in textile manufacturing industry, the variation among tensile strength measurements from thin thread is significantly smaller than measurements taken from heavy thread because of the inherent physical properties of fiber.…”
Section: Introductionmentioning
confidence: 99%